Satellite and information technology based flash flood generation studies in the urbanised zones - 347723 Wan Mokhtar Wan Nawang; Seminar Kebangsaan IRPA Rancangan Malaysia Kelima : Sektor Strategik (1991 : Pulau Pinang)
PSZJBL